Current application of seaweed waste for composting and biochar: A review. (May 2023) - Dang, Bao-Trong; Ramaraj, Rameshprabu; Huynh, Ky-Phuong-Ha; Le, Minh-Vien; Tomoaki, Itayama; Pham, Tan-Thi; Hoang Luan, Van; Thi Le Na, Pham; Tran, Duyen P.H.
Graphical abstract: Highlights: Seaweed derived-compost and biochar have distinct properties from terrestrial plants. Complex polysaccharides, moisture, metals, and C/N ratios affect compost production. Seaweed increases the earthworm cocoon and microbial consortium for vermicomposting. Biochar provides many functional groups for pollutant removal and soil amelioration. Pyrolysis temperature effects biochar yield, ash, O/C ratio, surface and porosity. Abstract: To address the origins of ocean acidification, seaweed aquaculture is emerging as a key biosequestration strategy. Nevertheless, seaweed biomass is involved in developing food and animal feed, whereas seaweed waste from commercial hydrocolloid extraction is dumped in landfills, which together limit the carbon cycle and carbon sequestration. This work sought to evaluate the production, properties, and applications of seaweed compost and biochar to strengthen the "carbon sink" implications of aquaculture sectors. Due to their unique characteristics, the production of seaweed-derived biochar and compost, as well as their existing applications, are distinct when compared to terrestrial biomass. This paper outlines the benefits of composting and biochar production as well as proposes ideas and perspectives to overcome technical shortcomings. If properly synchronized, progression in the aquaculture sector, composting, and biochar production, potentially promote various Sustainable Development Goals.